PENGARUH WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN PADA PT ASURANSI JIWA MANULIFE INDONESIA DI SURABAYA - Eldon, Davin; Nugroho, J.L. Eko; Widjaja, M.E. Lanny Kusuma (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study analyzes the influence of work-life balance, job satisfaction, work motivation, and organizational commitment on employee performance at PT Asuransi Jiwa Manulife Indonesia in Surabaya. This research uses the quantitative method using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the assistance of the SmartPLS 3 software. The data used in this research is primary data that was collected through questionnaires which was distribute to all employees working at PT Asuransi Jiwa Manulife Indonesia via google form. The sample in this research is 117 employees working at PT Asuransi Jiwa Manulife Indonesia that lives in Surabaya. This study shows that work-life balance, job satisfaction, work motivation, and organizational commitment have a positive and significant effect on employee performance. Keywords: Work-life Balance, Job Satisfaction, Work Motivation, Organizational Commitment, Employee Performance